2015
DOI: 10.1111/ijfs.13020
|View full text |Cite
|
Sign up to set email alerts
|

Development of microbiologically safe mung bean sprouts using combination treatment of sodium hypochlorite and gamma radiation

Abstract: Specific group of people, with impaired immune system, are recommended to consume pathogen-free foods. In this study, microbiologically safe ready-to-eat (RTE) mung bean sprouts were developed using combination treatment (CT) with 200 ppm sodium hypochlorite and 12 kGy dose of gamma radiation. Microbiological analysis of combination-treated sprout samples showed complete elimination (<10 CFU g À1 of sprouts) of microbial load in these samples, even during storage at 4°C up to 12 days. Combination treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Other techniques to ensure the hygienic safety of sprouts could include ionizing radiation treatment, electron beam (e-beam) or gamma ray irradiation [ 210 , 211 ], as well as their combination with sodium hypochlorite [ 212 ]. However, these techniques are subjected to limitations and are not approved in all countries; in addition, major drawbacks are represented by their detrimental effects on different seed growth parameters.…”
Section: Post-harvest Storage and Processing Effects On Sprouts Samentioning
confidence: 99%
“…Other techniques to ensure the hygienic safety of sprouts could include ionizing radiation treatment, electron beam (e-beam) or gamma ray irradiation [ 210 , 211 ], as well as their combination with sodium hypochlorite [ 212 ]. However, these techniques are subjected to limitations and are not approved in all countries; in addition, major drawbacks are represented by their detrimental effects on different seed growth parameters.…”
Section: Post-harvest Storage and Processing Effects On Sprouts Samentioning
confidence: 99%
“…The regulatory effect of phosphorus and molybdenum during carbohydrate metabolism and at the time of photosynthesis in leaves and other plant parts should be considered one of the important and majorly plant limiting factor of plant growth and development particularly when convert to reproductive portion of the plant (Kumawat et al, 2009). The increasing doses of phosphorus at these positions of the crops enhanced starch and sucrose ratio of the leaves and other reproductive organs of the plant (Nagar et al, 2008). Khattak et al (2004) observed more phosphorus contents in legume seeds as they enhance phosphorus doses.…”
Section: Phosphorus Concentration In Seeds and Straw (%)mentioning
confidence: 92%
“…Some authors also use biological methods of limiting the growth of pathogenic bacteria; such methods include the use of bacteriophages, bacteriocins and probiotic bacteria, mainly lactic acid bacteria. The combined methods (i.e., hurdle technology) bring the best results without significantly losing the quality of ready-to-eat sprouts [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Despite the effective sanitation treatment of the seeds, often they are re-inhabited by unwanted microflora during their cultivation.…”
Section: Introductionmentioning
confidence: 99%